2011
DOI: 10.1111/j.1600-0609.2011.01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin‐2 is associated with modulation of disease phenotype in a patient with concurrent JAK2‐V617F and BCR‐ABL mutation

Abstract: We investigated the role of lipocalin‐2 (LCN‐2) and its receptor (SLC22A17) in mediating clonal dominance in a patient with both BCR‐ABL and JAK2‐V617F mutations. LCN‐2 mRNA showed a near 50‐fold increase in expression, accompanied by down‐regulation of SLC22A17, coinciding with increase in BCR‐ABL transcripts, loss of JAK2‐V617F and change of clinical phenotype from polycythaemia vera to chronic myeloid leukaemia. These changes were reversed after commencing imatinib mesylate. Consistent with experimental stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…With regard to CML, inhibition of the constitutive tyrosine kinase activity of p210 BCR-ABL [ 51 ] with imatinib alleviates the hyperproliferation-induced symptoms [ 52 ]. Furthermore, serum levels of NGAL are significantly higher in CML patients than in healthy individuals [ 44 , 45 , 53 , 54 ]. If CML patients achieve complete molecular remission after imatinib therapy, NGAL serum levels fall and are significantly lower than during the full-blown disease [ 44 , 53 ].…”
Section: Ngal As a Biomarker In Cancermentioning
confidence: 99%
“…With regard to CML, inhibition of the constitutive tyrosine kinase activity of p210 BCR-ABL [ 51 ] with imatinib alleviates the hyperproliferation-induced symptoms [ 52 ]. Furthermore, serum levels of NGAL are significantly higher in CML patients than in healthy individuals [ 44 , 45 , 53 , 54 ]. If CML patients achieve complete molecular remission after imatinib therapy, NGAL serum levels fall and are significantly lower than during the full-blown disease [ 44 , 53 ].…”
Section: Ngal As a Biomarker In Cancermentioning
confidence: 99%
“…Our study provides the first evidence that the co-expression of NGAL-R and CD38 is a high-value target in CLL. Beyond CLL, the expression rates of CD38 and NGAL-R are high in other tumors such as acute and chronic myeloid leukemias [ 47 , 48 , 49 , 50 ], epithelial carcinomas (esophagus, liver, kidney, endometrial carcinomas) [ 13 , 24 , 51 , 52 , 53 , 54 , 55 ] and gliomas [ 51 , 56 ]. Although these studies separately showed elevated expressions of CD38 and NGAL-R, it is very likely that both antigens are co-expressed in these tumors, and therefore suggest that a combination of anti-CD38/NGAL-R Abs may offer new therapeutic options for the management of these cancers.…”
Section: Discussionmentioning
confidence: 99%